2022
DOI: 10.1002/nag.3443
|View full text |Cite
|
Sign up to set email alerts
|

Elliptical cylindrical equivalent model for consolidation of unsaturated soil improved by PVD

Abstract: To consider the shape effect of prefabricated vertical drain (PVD), the elliptical cylindrical equivalent model (ECEM) is established for the consolidation of unsaturated soft foundations improved by PVD. Then, the associated analytical solutions of excess pore-air and pore-water pressures are derived under free strain and equal strain conditions, respectively. The rationality of proposed solutions is verified by comparing them with the existing solutions. Through conducting the parametric study, the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…(4) The water flow obeys Darcy's law. (5) The equal strain condition from Barron et al 11 is followed in this model. (6) The bottom of the soil is impervious, and the top surface of the soil is pervious.…”
Section: Basic Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) The water flow obeys Darcy's law. (5) The equal strain condition from Barron et al 11 is followed in this model. (6) The bottom of the soil is impervious, and the top surface of the soil is pervious.…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…With the advancements in geosynthetics and vacuum preloading technology, prefabricated vertical drains (PVD) have become increasingly prevalent in ground improvement projects owing to their low cost and excellent performance. [1][2][3][4][5][6][7][8][9][10] Consolidation theory, which serves as the theoretical foundation for engineering designs, has long fascinated academics. Barron 11 first proposed the radial consolidation theory for soils improved with sand well, which did not account for well resistance and relied on several assumptions to arrive at an analytical solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analytical models of vacuum consolidation have been proposed, and the analytical theories are mainly based on the classical analytical models of sand drain consolidation 24,25,26,27,28,29 . Mohamedelhassan and Shang 30 indicated that the vacuum pressure can be treated as vertical pressure when establishing the analytical models of vacuum consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…23 Several analytical models of vacuum consolidation have been proposed, and the analytical theories are mainly based on the classical analytical models of sand drain consolidation. 24,25,26,27,28,29 Mohamedelhassan and Shang 30 indicated that the vacuum pressure can be treated as vertical pressure when establishing the analytical models of vacuum consolidation. Zhou et al 31 established an analytical model for the axisymmetric consolidation of soft soil under a surcharge and vacuum preloading, and analytical solutions for a multi-layer soil system were then obtained.…”
Section: Introductionmentioning
confidence: 99%